From the margins poverty portrayals in "Kapuso Mo, Jessica Soho" episodes (2019–2024) - Guillermo, Jhoi Angeline C.
In the Philippines, poverty is a persistent reality. Millions of Filipinos continue to be deprived of basic necessities and public services, which calls for broader media representation of their lived experiences in the hope of raising public awareness and sparking social change. But when profit-oriented mainstream media begin to hyperfocus on the emotional appeal of these stories, Filipino struggles are reduced to mere spectacles and poverty becomes a product meant for consumption. Guided by Roland Barthes’ Semiotics and Theodor Adorno and Max Horkheimer’s Culture Industry, this study examined how poverty stories are portrayed in mainstream media, particularly in Kapuso Mo, Jessica Soho (KMJS), through content analysis, interviews with key informants, and focus group discussion. Results show that KMJS is hugely shaped by everything that sells—featuring recurring poverty narratives and employing formulaic storytelling techniques. This, in turn, has the potential to perpetuate myths, such as glorified resiliency and individualization, which view poverty as a personal struggle rather than a systemic failure. Moreover, the show’s adherence to ethical guidelines is found to be inconsistent across episodes; some strictly uphold the standards, while others do not. As a result, this study suggests that the creation of local guidelines on poverty reporting is deemed necessary, alongside active consultation with grassroots communities and advocacy groups.